A two-year history of high bone loading physical activity attenuates ethnic differences in bone strength and geometry in pre-/early pubertal children from a low-middle income country - Meiring, R.; Avidon, I.; Norris, S.; McVeigh, Joanne (Elsevier Science, 2013)
We examined the interplay between ethnicity and weight-bearing physical activity on the content and volumetric properties of bone in a pre- to early pubertal South African Black and White population. Sixty six children [Black boys, 10.4 (1.4)yrs, n=15; Black girls, 10.1 (1.2)yrs, n=27; White boys, 10.1 (1.1)yrs, n=7; White girls, 9.6 (1.3)yrs, n=17] reported on all their physical activities over the past two years in an interviewer administered physical activity questionnaire (PAQ). All participants underwent a whole body and site-specific DXA scan and we also assessed bone structure and estimated bone strength with pQCT. Children were classified as being either high or low bone loaders based on the cohort's median peak bone strain score estimated from the PAQ. In the low bone loading group, Black children had greater femoral neck bone mineral content (BMC) (2.9 (0.08)g) than White children (2.4 (0.11)g; p=0.05). There were no ethnic differences in the high bone loaders for femoral neck BMC. At the cortical site, the Black low bone loaders had a greater radius area (97.3 (1.3) vs 88.8 (2.6)mm2; p=0.05) and a greater tibia total area (475.5 (8.7) vs. 397.3 (14.0)mm2; p=0.001) and strength (1633.7 (60.1) vs. 1271.8 (98.6)mm3; p=0.04) compared to the White low bone loaders. These measures were not different between the Black low and high bone loaders or between the Black and White high bone loaders. In conclusion, the present study shows that there may be ethnic and physical activity associations in the bone health of Black and White pre-pubertal children and further prospective studies are required to determine the possible ethnic specific response to mechanical loading. © 2013 Elsevier Inc.